¡A los Americanos! Deutsche Propaganda in Lateinamerika während des Ersten Weltkrieges (1914-1918) - Russ, Carla (Historamericana, 2022)
This study addresses German propaganda in Latin America during World War I from a transnational perspective. It shows that the propaganda was realized through a pluricentric network. The dependence on initiatives in Argentina, Chile and Mexico also had consequences for the discursive configuration.